ANALISIS FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Darmono, Darmono (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
The purpose of this study is to find out and analyze the factors that influence the dividend payout ratio in manufacturing companies in the Indonesia Stock Exchange.The research data used in this study is secondary data. The population in this study is a manufacturing company with a total sample of 17 manufacturing companies on the Indonesia Stock Exchange. Data analysis was carried out by multiple linear regression methods. The results of the analysis show that the free cash flow variable, return on investment, debt to equity ratio, and total assets turnover, simultaneously have an influence on the dividend payout ratio in manufacturing companies on the Indonesia Stock Exchange.